2012
DOI: 10.1143/jjap.51.032701
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive In-vivo Measurements of Microvessels by Reflection-Type Micro Multipoint Laser Doppler Velocimeter

Abstract: We have developed a micro multipoint laser Doppler velocimeter (µ-MLDV) that enables selective collection of Doppler interference photons. In previous report [H. Ishida et al.: Rev. Sci. Instrum. 82 (2011) 076104], developed the reflection-type µ-MLDV, and showed the results of demonstrations performed on transparent artificial flow channels. In this study, we attempted to perform in-vivo experiments using animals. It can measure absolute velocity and generate tomographs of blood vessels courses. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In a previous study, we demonstrated that an L-MLDV system could be used to visualize the blood flow in the capillaries of a mouse [28][29][30]. However, the values in our velocity images were averaged over the measurement period (1.0 s), and the possibility of simultaneous blood flow measurements at all points in the imaged area was not discussed.…”
Section: Results Of Pulsatile L-mldv In the Carotid Arterymentioning
confidence: 93%
“…In a previous study, we demonstrated that an L-MLDV system could be used to visualize the blood flow in the capillaries of a mouse [28][29][30]. However, the values in our velocity images were averaged over the measurement period (1.0 s), and the possibility of simultaneous blood flow measurements at all points in the imaged area was not discussed.…”
Section: Results Of Pulsatile L-mldv In the Carotid Arterymentioning
confidence: 93%